Does professional identity play a critical role in the choice to remain in the nursing profession? - Margareth Kristoffersen (Wiley, 2021)
Abstract Aim To explore aspects of professional identity in nurses' written narratives of what is significant to their choice to remain in the profession. Design This study used a qualitative design and was underpinned by a hermeneutical approach. Methods The participants were recruited via purposive sampling procedures and included 13 nurses aged 26 to 62 years. The data were collected in the form of written narratives to initiate the nurses' reflections on the decision to remain in the profession. A thematic analysis was conducted. Results The analysis revealed two themes: acting as a professional contributor and realigning to maintain professional belongingness. In the nurses' written narratives, these aspects of professional identity were clearly significant to their choice to remain in the profession. In a complexly interwoven way, the aspects constructed who the nurses were as professionals, and thus, professional identity seems to play a critical role in the choice to remain.